COMBINATION EFFECT OF LISINOPRIL AND DILTIAZEM AS ANTI FIBROSIS IN PERITONEUM OF RATS - Putranto, Wachid; Effendi, Imam; Kusmardi, Kusmardi; Shatri, Hamzah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this research was to evaluate the effect of combination between lisinopril and diltiazem in reducing expression of transforming growth factor-Î² (TGF-Î²) and fibrosis peritoneum in a male rat treated with continuous ambulatory peritoneal dialysis (CAPD). Method: This was an experimental study, post-test only control group design. Thirsty Dawley Sprague rats are divided into five groups: Control group (Group 1), CAPD liquid 4,25% (Group 2), lisinopril 1.44 mg oral and CAPD (Group 3), and diltiazem CD 6.48 mg oral and CAPD (Group 4), lisinopril 1.44 mg+diltiazem CD 6.48 mg oral and CAPD (Group 5). After 4 weeks, rats sacrificed expression of TGF-Î² and peritoneal fibrosis are conducted by histopathology with hematoxylin-eosin staining and immunology with anti-human-TGF-Î². Result: Twenty peritoneal of rats can be examined. Mean score of TGF-Î² in control group is 1, 8, in CAPD group is 2, in lisinopril and CAPD group is 1, 8, in diltiazem CD and CAPD group is 1, 8, in lisinopril and diltiazem CD and CAPD group is 1, 7 (p=0.959). Mean score of peritoneal fibrosis in control group is 1, 1, in CAPD group is 2, 6, in lisinopril and CAPD group is 1, 2, in diltiazem CD and CAPD group is 1, 3, in lisinopril and diltiazem CD, and CAPD group is 1, 5 (p=0,268). Conclusion: Combination of lisinopril and diltiazem lower the expression of TGF-Î² and peritoneum fibrosis better than lisinopril or diltiazem but statistically not significant. Combination of lisinopril and diltiazem lower the peritoneal fibrosis but statistically not significant, and it does not better than lisinopril or diltiazem.